2005
DOI: 10.1109/tro.2005.847610
|View full text |Cite
|
Sign up to set email alerts
|

Biped gait generation and control based on a unified property of passive dynamic walking

Abstract: Abstract-Principal mechanisms of passive dynamic walking are studied from the mechanical energy point of view, and novel gait generation and control methods based on passive dynamic walking are proposed. First, a unified property of passive dynamic walking is derived, which shows that the walking system's mechanical energy increases proportionally with respect to the position of the system's center of mass. This yields an interesting indeterminate equation that determines the relation between the system's cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 15 publications
(36 reference statements)
3
72
0
2
Order By: Relevance
“…Some of the most recent biped dynamics and controls research has been reported in the following references [10], [14], [15], [16], [17], [18], and [19]. Optimization techniques [20], [21], [22], [23] have become very popular in the pursuit of finding specific optimized swing leg trajectories.…”
Section: Control Approachesmentioning
confidence: 99%
“…Some of the most recent biped dynamics and controls research has been reported in the following references [10], [14], [15], [16], [17], [18], and [19]. Optimization techniques [20], [21], [22], [23] have become very popular in the pursuit of finding specific optimized swing leg trajectories.…”
Section: Control Approachesmentioning
confidence: 99%
“…Inspired by the idea of passive walking, researchers focused on designing prototypes and walking gaits to achieve efficient walking. To be specific, various other methods have been proposed to regulate full-actuated robots' walking gaits, [6][7][8][9][10] while several passivity-based control methods have been designed to stabilize the unstable walking gaits. 11,12 However, since the full-actuated biped robots mentioned above are equipped with flat feet and foot rotation is forbidden, the application of robot dynamics is limited and the efficiency is still not high enough.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the total energy-shaping control for the passive biped robot has been proposed to enlarge the basin of attraction and increase the rate of convergence [11]. A virtual gravity field is introduced to act as a driving force, which realizes the virtual passive walking on level ground [12]. The reinforcement learning-based method was used to control the robot to walk on an uneven floor [13,14].…”
Section: Introductionmentioning
confidence: 99%